ANALISIS YURIDIS PERANAN DINAS PERHUBUNGAN KOTA BATAM DALAM MEWUJUDKAN PERLINDUNGAN HUKUM BAGI PENUMPANG ANGKUTAN UMUM (STUDI PENELITIAN DI KANTOR DINAS PERHUBUNGAN KOTA BATAM) - Goa Pranabetara Lubis; Christiani Prasetyasari; Siti Nurkhotijah (Ensiklopedia of Journal, 2022)
People’s lives in urban areas still dependon the presence of public transportation, although there are still many who still use public transportation are office workers or school children, because taking public transportation can be considered to save time and save costs. But unfortunately we still see public transport accidents on the streets, this should not continue to happen because public transportation is very close to the community. Therefore, the Batam city transportation service will prevent public transport accidents from happening again. So this research is important to do in order to know how the role of the Batam city transportation service in carrying out their duties and obligations in cracking down on public transportation. Public transport passengers also hope that the Batam city transportation service will firmly take action on public transport that does not follow road-worthy rules so that it can minimize public transport accidents. This research uses normative and empirical methods and data collected by means of a legal approach and also with the legislation which is the legal basis and there are also interviews. The results of the research conducted indicate that the legal arrangements carriedout by the Batam city transportation service use law No. 22 of 2009 concerning road traffic & transportation. The constraint factor in this problem is that public transport drivers still do not check or inspect their vehicles before they are declared roadworthy. The suggestion in this study is that the Batam city transportation service must be firm in cracking down on public transportation that is not roadworthy so that passengers hope that public transportation accidents due to unsuitable public transportation condictions can be reduced for the safety and comfort of public passenger transportation in Batam city.Keywords: Legal Protection, Passenger, Transport Public, Communication